Implementasi Pembelajaran Akidah Akhlak dalam Membentuk Kepedulian Sosial dan Karakter Rendah Hati Peserta Didik Kelas V Di Madrasah Ibtidaiyah Darud Da’wah Wal Irsyad Bottoe Kecamatan Tanete Rilau Kabupaten Barru - Nurung, Saripa; Shaleh, Muhammad; Saputra, Imran (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2025)
This study aims to analyze the implementation of the Akidah Akhlak learning program and its impact on shaping the character of social concern and humility among fifth-grade students at Madrasah Ibtidaiyah Darud Da’wah Wal Irsyad Bottoe. A qualitative research approach was employed, with data collected through in-depth interviews with the head of the madrasah, Akidah Akhlak teacher, classroom teachers, and parents, as well as through participatory observation and documentation studies. The findings show that the implementation of Akidah Akhlak learning at MI DDI Bottoe is well-planned, age-appropriate, and integrates local values. Experiential learning and discussion methods serve as the main approaches, supported by value inculcation through exemplary stories and routine practices within the madrasah environment, such as congregational Dhuha prayers and classroom duties. Student character evaluation is conducted qualitatively, focusing on individual development. However, the madrasah faces several challenges, including limited instructional time, differing parental understanding, and the negative influence of social media. The key findings reveal a positive and significant impact of Akidah Akhlak learning on students’ behavioral changes. In terms of social concern, students demonstrate greater initiative in helping friends and neighbors, as well as an increased willingness to share. Regarding humility, students become more open to feedback, avoid showing off, and learn to appreciate the contributions of others to their achievements. Consistency in habituation at school and exemplary behavior from families play crucial roles in strengthening the internalization of these values. This study concludes that Akidah Akhlak learning is effective in shaping students’ noble character.